ANALISIS YURIDIS PENANGANAN PEKERJA MIGRAN NON PROSEDURAL OLEH PELAYANAN PELINDUNGAN PEKERJA MIGRAN INDONESIA KOTA PAREPARE - Sunita, Sunita; Rasyid, Wahyu; Abejo, Dodie Baltazar Taher (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Indonesia is one of the largest countries that sends its citizens to work abroad. However, many of them experience injustice in their rights and experience inappropriate treatment. This study has two problem formulations, namely How is the legal analysis of the handling of non-procedural Indonesian migrant worker practices based on Law No. 18 of 2017 concerning the protection of Indonesian migrant workers, and How are the efforts of the Indonesian Migrant Worker Protection Service Post P4MI to repatriate non-procedural Indonesian migrant workers. The purpose of this study is to find out how the legal analysis of the prevention and handling of non-procedural Indonesian migrant worker practices is based on Law No. 18 of 2017 concerning the protection of Indonesian migrant workers, and to find out how the efforts of the Indonesian Migrant Worker Protection Service Post (P4MI) to repatriate non-procedural Indonesian migrant workers. This study uses a type of empirical normative research. The data collection techniques used are literature studies, field studies and interviews. From the results of this study, it can be concluded that the role of the Ministry of Protection of Indonesian Migrant Workers (P2MI) in seeking protection for Indonesian migrant workers